Distribuição e biodisponibilidade de nutrientes em albufeiras na República Dominicana e seu papel na recuperação de solos erodidos por eventos climáticos extremos - fonseca, Rita (2018)
The sustainable concept of use of dam reservoir sediments to improve the soil quality is particularly suitable for reservoirs in the Dominican Republic, characterized by high sedimentation rates due to the over erosion of drainage basins, some of them in steep slopes areas and with low soil cover, intensified by periods of extreme hydrometeorological events occurring almost every year. Studies of nutrient determination in two Dominican reservoirs, situated under different climatic conditions, revealed that, although there isn’t a marked increase of nutrients in inorganic and organic forms, in sediments when compared with parental soils, the most available fractions, namely Ca and Mg in solution and exchangeable complex, N in the nitrate form, and available P and K, have significantly higher values than those of the nearby soils, as a consequence of the selective erosion of the finer and lower density particles of the soils and of the greater biological activity in the lakes. Extraction and use of these sedimentary materials in subsistence agriculture, in addition to improving soil quality and the living conditions of small farmers, could improve the water quality and increase the lifespan of the reservoirs.